Old Sumerian and Old Akkadian Texts in Philadelphia. Part Two: The 'Akkadian' Texts, the Enlilemaba Texts, and the Onion Archive - Westenholz, Aage (1987)
The Carsten Niebuhr Institute of Ancient Near Eastern Studies, University of Copenhagen; Part One = 37:171, 1975.